Anatomy Education Environment Measurement Inventory (AEEMI): a cross-validation study in Malaysian medical schools - Siti Nurma Hanim Hadie; Muhamad Saiful Bahri Yusoff; Wan Nor Arifin; Fazlina Kasim; Zul Izhar Mohd Ismail; Mohd Anizam Asari; Husnaida Abdul Manan @ Sulong; Asma’ Hassan; Tg Fatimah Murniwati Tg Muda; Yasrul Izad Abu Bakar; Rasheeda Mohd Zamin; Elvy Suhana Mohd Ramli; et al. (BioMed Central Ltd., 2024)
Indexed by WOS/SCOPUS/ERA